Trend 2000 - 2012. Statistics Canada. CANSIM: Economic Accounts - Government Financial Statistics | Country: Canada | Province: Northwest Territories | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Beer, Canadian products, Total sales, Value in dollars | Units: , 2000-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-060. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Economic Accounts - Government Financial Statistics | Country: Canada | Province: Northwest Territories | Table: Sales of alcoholic beverages by volume, value and per capita 15 years and over, fiscal years ended March 31 | Variable: Beer, Canadian products, Total sales, Value in dollars | Units: , 2000-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-060. Dataset: Presents financial statistics on the Canadian government, including employment and remuneration, revenues and expenditures, balance sheets, government business enterprises, and classification of public sector entities. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Government and Politics Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Federal Employment, Government Receipts, Economic Conditions, Economy, Federal Government, Government Spending